Mito y reescritura: Medea y Ulises en los textos ovidianos del exilio (Argos, 2025)
This paper proposes a reading of two mythical emblems of Ovid's exilie poetry, Medea and Ulysses. Our aim is to illustrate the dynamics of the myth, which can be adapted to every context because of its flexibility. In the specific case of Tristia and Epistulae ex Ponto the inclusion of myth and legend allows to stress several aspects of the poet's "subjective" experience. Medea and Ulysses become the symbols of two central imageries of Ovid's exile: the motif of dismembering and that of an erratic journey with generic implications.
Keywords: myth; rewriting; transformation; Ovid; exile